Utilization of Instagram Social Media in Repairing Image of Anyer Beach Tourism - Indah Pratiwi; Annisarizki; Dwi Nurina Pitasari (Politeknik Pariwisata Palembang, 2021)
This study aims to determine the use of Instagram social media in improving the image of Anyer beach tourism through organizing the Anyer Krakatau Culture Festival event and promoting it to the public through the Instagram account @akcf_official. This research uses a case study method with a qualitative approach. The determination of the informants was carried out using a purposive sampling technique with three informants as key informants and one informant as secondary informants. Data collection techniques using observation, interviews, literature study and documentation. The validity technique is done by data triangulation. The theory used in this study is the CMC (Communication Mediated Computer) theory and using the PR Transfer Process model.